The economic paradigm - Towfigh, Emanuel; Petersen, Niels (Economic Methods for Lawyers, 2015)
The discipline of economics nowadays is not so much characterized by its object of investigation, but rather by its methodological approach. This approach is shaped by a number of ideas, concepts, and assumptions that underlie most aspects of economic thought and that are also the basis of the economic analysis of the law. We refer to this perspective as the ‘economic paradigm’. The economic paradigm encompasses a number of overarching ideas. First, from a methodological perspective, economists generally focus their study on individual behavior rather than, for example, on ‘systems’ (that may consist of individuals but where individual behavior is not the main descriptor) or ‘neuro-cognitive mechanisms’ (the processes that drive individual behavior); this is called methodological individualism. Moreover, economists assume that resources are scarce, which is why individuals face choice problems. How do people solve these choice problems? In line with methodological individualism and the scarcity assumption, economists have developed the behavioral model of the homo economicus: The idea is that individual actors behave rationally in that they choose decisions that maximize their individual utility. This model of homo economicus has been criticized with various valid arguments; however, in the absence of an equally conclusive alternative behavioral model, it is still the prevalent concept in economics, and therefore also in the economic analysis of law.